Web Presence of Selected Iconic Public Libraries’ of India: Webometric Analysis - Brahma, Krishna; Kumar Verma, Manoj (International Journal of Information Studies, 2025)
The present study examines the websites of Selected Iconic Public Libraries’ in India. There are 11 Iconic public libraries in India, out of which 9 libraries are having their websites. The study analyses the total number of webpages, domain authority, equity-links, internal, external links and web impact factor and to rank it. The study explored that the National Library of India tops with highest Page Authority (21%), Total Linking Root domains (68%), highest External EquityPassing Links (97%), Total Equity- Passing Links (88%), Total External Links (97%), Total Links (87%), Followed Linking Root Domains (68%) and with highest Linking C Blocks (68%).Nehru Memorial Museum and Library also scores at top position with highest Internal Equity-Passing Links (90%) and Total Internal Links (90%). Thus, it can be interpreted that the overall WIF of National Library of India is at top most position with 92.90SWIF & EWIF, on the other hand, Nehru Memorial Museum and Library stands at second place with with15.82 SWIF and 15.35 IWIF among 9 selected Iconic Public libraries’ of India.